Utilization of Digital Technology and Review of the Role of Guidance and Counseling Teachers in Managing Students' Psychological Crisis - Rike Ernawati Sinaga; Yeni Karneli; Mudjiran; Ramdani (Quality : Journal Of Education, Arabic And Islamic Studies, 2025)
The development of digital technology has had a huge impact on students' lives, both positive and negative, affecting their mental health. Challenges such as cyberbullying, social media addiction, and academic pressure due to social comparison add to the complexity of the psychological crisis experienced by students. Guidance and Counseling (BK) teachers have an important role in helping students deal with this crisis, by developing relevant approaches, as well as utilizing technology in counseling services. In the digital era, technology-based interventions, such as cybercounseling, can facilitate students' access to counseling services and increase the effectiveness of psychological support. This article discusses the literature on the role of counseling teachers in managing students' psychological crisis in the digital era, as well as the necessary competencies and intervention strategies. With support from various parties, including schools and families, counseling teachers can help create an environment that supports students' holistic mental health, while optimizing the use of technology in counseling services.